THE CHALLENGE OF TREATING EPILEPSY IN PREGNANCY: MATERNAL AND OFFSPRING PERSPECTIVES - Babikir, Haydar E. (Gezira Journal of Health Sciences, 2010)
Epilepsy is a common medical and social disorder and usually defined as a tendency to recurrent seizures. Freedom from seizures is the ultimate goal in treatment of patients with epilepsy. At the same time, the side effects of antiepileptic drugs (AEDs) should not outweigh the benefits of treatment. This is particularly important in epileptic women who wish to become pregnant. Those women have a higher risk for pregnancy-related complications. For babies whose mothers take AEDs, the risk of birth defects is 4 to 8 percent, compared with 2 to 3 percent for controls. The risk seems to be highest when multiple AEDs are taken, but without medication, uncontrolled seizures may deprive the baby of oxygen. Seizures can also increase the risk of miscarriage or stillbirth. By working with her physicians, a woman with epilepsy can become pregnant and have a happy outcome.